POTENSI POTENSI GENOTIPE UNGGUL PADI GOGO (Oryza sativa L.) BERDASARKAN KARAKTER VEGETATIF UNTUK MENINGKATKAN KETAHANAN PANGAN - Syaifullah Rahim; Gusti Ray Sadimantara; Muhidin Muhidin; Nandini Ayuningtias; Amin Mbusango (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2025)
[EVALUATION OF SUPERIOR RICE GENOTYPES (Oryza sativa L.) BASED ON VEGETATIVE CHARACTERISTICS TO ENHANCE FOOD SECURITY]. This study aimed to identify superior genotypes of upland rice (Oryza sativa L.) adaptable to dryland conditions to support national food security. The experiment was conducted in Kambu Subdistrict, Southeast Sulawesi, using a Randomized Complete Block Design (RCBD) with four replications. Eight genotypes were evaluated for five vegetative parameters—plant height, number of leaves, number of tillers, leaf area, and days to flowering measured at 21-77 days after planting (DAP). Significant genetic variation was observed among genotypes. Genotypes GS11-2, GS44-1, and GS16-1 exhibited superior early growth,with plant heights of 58-60 cm at 35 DAP, significantly outperforming the local control (41.6 cm). Correlation analysis revealed a strong positive relationship between plant height and leaf area (r=0.94 at 49-77 DAP) and a significant negative correlation between plant height and number of tillers (r=-0.86). Coefficients of variation ranged from 8.5-19.5%, indicating reliable data, except for leaf area at 21 DAP (30.1%). These findings underscore the value of early selection based on vegetative traits, particularly plant height and leaf area, as reliable indicators of yield potential. Genotypes with rapid and stable vegetative growth hold promise for development as dryland-adapted varieties. This research provides a robust scientific foundation for upland rice breeding programs to address land conversion and climate change challenges, thereby enhancing national food resilience. Full txt pdf